Performance Analysis of Patch Antenna for Ultra-Wideband using Particle Swarm Optimization - Elechi, Promise; Orike, S.; Ikpo, C.E. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2021)
Recently, with the rapid development of fixed and portable communication systems, there is a need for very high data rates for short-distance transmissions. Ultra-Wideband (UWB) is a wireless technology that offers the advantage of low power consumption, high data rate, high time resolution, lowcost implementation, obstacle penetration, resistance to interference and co-existence with narrowband systems. To harness the benefits and advantages of UWB technology, a suitable antenna needs to be designed. In this study, a patch antenna fed by a microstrip line designed on a substrate is considerably studied and analysed for use within the UWB frequency range of 3.1GHz -10.6GHz. The antenna has been designed and simulated using COMSOL Multiphysics Software at varying frequencies using derived geometric parameters. Particle Swarm Optimization (PSO) technique was used to optimise the modelled patch antenna to achieve optimal antenna performance. Modelling and optimisation of the presented microstrip patch antenna produced results that are suitable for UWB applications.